2017
DOI: 10.1103/physrevx.7.011005
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Magnetic Response at Optical Frequencies Using Atomic Transitions

Abstract: In optics, the interaction of atoms with the magnetic field of light is almost always ignored since its strength is many orders of magnitude weaker compared to the interaction with the electric field. In this article, by using a magnetic-dipole transition within the 4f shell of europium ions, we show a strong interaction between a green laser and an ensemble of atomic ions. The electrons move coherently between the ground and excited ionic levels (Rabi flopping) by interacting with the magnetic field of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
(60 reference statements)
2
5
0
Order By: Relevance
“…Using the inferred value of the coupling laser Rabi frequency from the fit (Ω C = 2π × 350 kHz), we calculate the magnetic-dipole matrix element for the specific hyperfine transition to be µ = (0.10 ± 0.01)µ B (µ B is the Bohr magneton). This is reasonably consistent with the hyperfine-averaged matrix element measurements of our previous Rabi flopping experiments [40].…”
Section: Ion Class Selectionsupporting
confidence: 92%
See 2 more Smart Citations
“…Using the inferred value of the coupling laser Rabi frequency from the fit (Ω C = 2π × 350 kHz), we calculate the magnetic-dipole matrix element for the specific hyperfine transition to be µ = (0.10 ± 0.01)µ B (µ B is the Bohr magneton). This is reasonably consistent with the hyperfine-averaged matrix element measurements of our previous Rabi flopping experiments [40].…”
Section: Ion Class Selectionsupporting
confidence: 92%
“…By imaging the excitation profile of europium-doped nanoparticles at room temperature, they conclusively demonstrated the magnetic-dipole nature of this transition. We recently observed strong-field Rabi flopping on this transition at cryogenic temperatures [40]. Using angle-dependent fluorescence, we also confirmed that the electrons interacted with the magnetic field of light as they were being excited.…”
Section: Rare-earth Doped Crystalssupporting
confidence: 65%
See 1 more Smart Citation
“…Nevertheless, certain quantum emitters, such as rare‐earth ions and semiconductor quantum dots , possess prominent MD transitions whose strength is comparable or even greater than the competing ED ones. Very recently, Rabi oscillations of these transitions driven by a coherent external wave were reported . Growing interest of researchers in such emitters poses a challenging quest for nanostructures which can enable an enhanced interaction of light with MD quantum emitters and potentially lead to novel optical devices fully exploiting the magnetic nature of light.…”
Section: Introductionmentioning
confidence: 99%
“…By using measurement samples sufficiently smaller than the wavelength, which can be easily achieved nowadays, we can control the applied electric and magnetic fields almost independently. In particular, we can avoid strong electric dipole absorption which often overwhelms magnetic absorption which we are interested [27].…”
Section: Introductionmentioning
confidence: 99%